IMPLEMENTATION OF QUALITATIVE VALUE FOR MONEY ANALYSIS FRAMEWORK IN THE AVAILABILITY PAYMENT SCHEME FOR INFRASTRUCTURE DEVELOPMENT AT REGENCY / CITY LEVEL CASE STUDI: BANDUNG STREET LIGHTNING - Alexander Tanne, Yongki
Infrastructure development is one of the strategic policies of the Indonesian government in order to increase economic and social growth. This can be seen from the budget allocation for infrastructure development which continues to increase from 256.1 Trillion Rupiah (2015) to 423.3 Trillion Rupiah (APBN 2020). Indonesia's infrastructure competitiveness ranking (CGI, 2019) still lags behind in the Southeast Asia (ASEAN) region behind Singapore, Malaysia, Brunei, Thailand and is ranked 72 out of 141 countries globally. The Indonesian government proposes a new paradigm in infrastructure funding (Bappenas, 2018) by making the APBN / APBD the last resource. The government then encourages the role of the private sector through the Public Private Partnership (PPP) scheme, both User Payment and Availability Payment (AP). Infrastructure procurement under the AP scheme is still rarely carried out, especially by local governments at the Regency / City level (only Bandar Lampung Water Supply and West Semarang Water Supply have been implemented). Several cities have started trying to apply the AP scheme, one of which is Bandung City with the Public Street Lighting Project. Value for money analysis (qualitative and quantitative) is needed to provide information on whether the AP scheme is better than traditional schemes, especially for social infrastructure that will be implemented by the AP scheme (World Bank, 2013). The limitations of historical data and the necessary assumptions make a quantitative VfM analysis need to be complemented by a qualitative VfM analysis. This study aims to identify criteria and implement qualitative VfM analysis, evaluate stakeholder perceptions of qualitative VfM criteria and evaluate AP scheme plans in the context of qualitative VfM. The case study in this research was carried out on the Bandung City Street Lighting project. An ordinal questionnaire was used to obtain an overview of stakeholder perceptions and understanding of the qualitative VfM criteria. Criteria that are classified as the main criteria are those that have a significance value of> 50% with the assumption that more than half of the respondents agree that these iv criteria are more important than others, while the criteria ? 50% are classified as supporting criteria and become a perception evaluation. The interview method is used to obtain important notes from evaluating the implementation of the AP scheme in the context of qualitative VfM in the PJU project in Bandung City. Implementation of qualitative VfM analysis includes economic and financial aspects; technical; social; politics and law; as well as managerial and government institutions and carried out at the planning stage of the AP scheme. Stakeholders' perceptions and understanding in the conception of the qualitative VfM criteria for the AP scheme for the PJU City of Bandung project are quite good although there are several notes, including the need for a common perception regarding the income from infrastructure operations as a determining factor in the use of the AP scheme; need the involvement of investors / private parties who have experience with AP schemes; need attention to environmental factors in project implementation so as not to damage; the need for regional head political policies based on long-term needs; as well as commitment from government employees in implementing the AP scheme. Evaluation of the AP scheme in the PJU City of Bandung project in the context of qualitative VfM, namely the need to improve the existing PJU technical data regarding the quality of availability and the number of PJUs to determine the project scope and cost estimates; need a comprehensive public consultation to see the social impact of the project; It needs DPRD involvement from the start of the planning and preparation of the PPP organization in accordance with the applicable regulations.